Pemanfaatan Ekstrak Belimbing Wuluh (Avverhoa bilimbi L.) Menjadi Sabun Cuci Piring - Zakiyah Darajat; Dian Ranggina; Harun Pampang; Afriyanti S. Lamuru; Muhammad Arham Yunus; Maria Assumpta Nogo Ole; Nurfiansyah Nurfiansyah (Universitas Pahlawan Tuanku Tambusai, 2022)
Wuluh star fruit is a plant that is rich in benefits. The population of this plant is very abundant in the community both in the yard or as a shade plant in the yard. The population of this plant is not proportional to its utilization so that the star fruit usually falls and rots. Seeing this, a community service activity was carried out regarding the use of starfruit into dish soap, which besides being able to add to the economic value of starfruit, can also reduce environmental pollution. Wuluh star fruit (Averrhoa bilimbi L.) contains saponins, flavonoids, acetic acid, and vitamin C. Saponins have the ability to kill bacteria while flavonoids can destroy bacterial proteins by lysis method so that bacteria cannot reproduce and die. Saponins also function as a foam producer so that they can be used in the manufacture of dish soap. Keywords: Wuluh star fruit, saponin, dish soap